Estimasi Tourism-Led Growth Hypothesis di Kabupaten Manggarai: Studi Peran Pariwisata Dalam Pertumbuhan Ekonomi - Yohanes Vianney; Kordianus Larum; Yosefina Ferda Lendo (Global Sustainability Research Institute, 2026)
Introduction: Tourism is considered one of the strategic sectors capable of stimulating regional economic growth through increased economic activities, employment opportunities, and local revenue. However, empirical evidence regarding the validity of the Tourism-Led Growth Hypothesis (TLGH) at the regional level, particularly in Manggarai Regency, remains limited. This study aims to examine the applicability of the TLGH in Manggarai Regency by integrating quantitative and qualitative approaches. Methods: This study employed a mixed-method approach. The quantitative analysis utilized the Vector Error Correction Model (VECM) based on time-series data obtained from Statistics Indonesia (BPS), while the qualitative analysis was conducted through in-depth interviews with tourism business actors and local policymakers to strengthen the interpretation of the econometric findings. Results: The findings reveal a long-run equilibrium relationship between tourism development and economic growth in the service sector. Tourist arrivals and tourism-generated local own-source revenue (PAD) have positive and significant effects on the service sector's Gross Regional Domestic Product (GRDP) in both the short and long run. Furthermore, the Granger causality test supports the validity of the Tourism-Led Growth Hypothesis in Manggarai Regency. Qualitative findings further indicate that tourism has generated tangible economic benefits for local MSMEs and accommodation providers, although the distribution of these benefits remains constrained by inadequate infrastructure, limited human resource capacity, and uneven tourism development policies. Conclusion and Suggestion: The study confirms that tourism serves as a significant driver of regional economic growth in Manggarai Regency, supporting the validity of the Tourism-Led Growth Hypothesis. To maximize tourism's contribution to inclusive and sustainable regional development, policymakers should prioritize infrastructure improvement, strengthen community-based tourism human resource development, optimize tourism revenue management, and reinforce local institutional capacity to ensure a more equitable distribution of tourism benefits.